Facile fabrication of highly sensitive and non-label aptasensors based on antifouling amyloid-like protein aggregates. Issue 24 (1st June 2022) - Ye, Xiangyi; Zhang, Dun; Zeng, Yan; Wang, Yingwen; Qi, Peng
Abstract : In this paper, we present a robust and versatile method for developing non-label aptasensors with high sensitivity. Abstract : In this paper, we present a robust and versatile method for developing non-label aptasensors with high sensitivity. Amyloid-like protein aggregates were facilely synthesized with the commonly used passivating agent bovine serum albumin (BSA) in developing biosensors, and the produced amyloid-like phase-transited BSA (PTB) exhibited excellent antifouling performances and robust interfacial adhesion with the electrode surface. In order to improve the detection sensitivity of electrochemical measurements, reduced graphene oxide was electrochemically deposited onto the electrode surface. Moreover, gold nanoparticles were introduced to enhance the conductivity of the PTB film and facilitate subsequent aptamer modification. Two common biological species, adenosine triphosphate (ATP) and cytochrome c (cyt c), were chosen as detection targets, and their corresponding aptasensors were successfully constructed and systematically evaluated. The proposed aptasensors based on the PTB–Au antifouling composite exhibited high sensitivity and specificity towards ATP and cyt c detection, and the detection limits were calculated to be 0.26 nM and 0.64 nM for ATP and cyt c, respectively. Hence, this work provides a simple approach to develop highly sensitive aptasensors without any labeling process, and thus promises its great application in biological analysis.